AUDIT FUNGSI MANAJEMEN PADA DISTRIBUTOR GAS LPG 3 KG PT. TRIPLE G KOTA PALEMBANG - Saladdin Wirawan Effendy; Poppy Indriani (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is to audit the management functions at the 3 kg LPG gas distributor PT. Triple G in Palembang City. This research is qualitative, where to obtain an overview and company data, the researcher conducted direct interviews with competent personnel, in-depth observations of indicators causing problems, and then drew conclusions. Based on the research results, it shows that management functions have not been well or effectively implemented by PT. Triple G. This condition can be seen from the poor financial and operational conditions, indicated by the absence of profits for shareholders, loss of potential income, and warnings from Pertamina Patra Niaga regarding the company's administrative governance. This condition will greatly impact the company's current and future operations